Zinc oxide nanoparticles foliar use and arbuscular mycorrhiza inoculation retrieved salinity tolerance in Dracocephalum moldavica L. by modulating growth responses and essential oil constituents - Zahra Ghaffari Yaichi; Mohammad Bagher Hassanpouraghdam; Farzad Rasouli; Mohammad Ali Aazami; Lamia Vojodi Mehrabani; Samaneh Fathpour Jabbari; Mohammad Asadi; Ezatollah Esfandiari; Silvia Jimenez-Becker (Scientific Reports)
Abstract The production of medicinal plants under stressful environments offers an alternative to meet the requirements of sustainable agriculture. The action of mycorrhizal fungus; Funneliformis mosseae and zinc in stimulating growth and stress tolerance in medicinal plants is an intriguing area of research. The current study evaluated the combined use of nano-zinc and mycorrhizal fungus on the physiochemical responses of Dracocephalum moldavica under salinity stress. The study employed a factorial based on a completely randomized design with three replications. The treatments were different levels of salinity (0, 50, and 100 mM NaCl), two levels of mycorrhiza application (0 and 5 g kg− 1 of soil), and two levels of foliar spraying of nano zinc oxide (0 and 1000 ppm). Salinity decreased the photosynthetic pigments content, SPAD value, and chlorophyll fluorescence data (Fm, Fv, Fv/Fm). Plant dry weight, Na + content, and essential oil content were significantly higher at 50 mM salinity + co-application of mycorrhiza and nano zinc oxide. Electrolyte leakage increased under salt stress, while mycorrhizal inoculation compensated for the trait. The main essential oil constituents were geranyl acetate, nerol, geranial, geraniol, viridiflorol, hexadecane, humulene, and germacrene D. Energy metabolism demonstrates the effectiveness of treatment combinations in promoting the biosynthesis and accumulation of essential oil components. The overall results with more comprehensive field-based studies would be advisable for the extension section to utilize marginal salty lands for the reliable production of a valuable medicinal plant.